Risk Factors Associated With Early-Onset Colorectal Neoplasm in Chinese Youth: A Prospective Population-Based Study - Shen, Jie; Wu, Yiling; Mo, Miao; Feng, Xiaoshuang; Zhou, Changming; Wang, Zezhou; Cai, Guoxiang; Zheng, Ying (Frontiers in Oncology, 2021)
Objective: Evidence of the risk factors associated with early-onset colorectal neoplasm from prospective population-based studies is limited. Our study aims to investigate the risk factors associated with early-onset colorectal neoplasm in Chinese youth using data from a prospective screening cohort. Methods: We enrolled 17,293 participants younger than 50 years from Shanghai colorectal cancer (CRC) screening program cohort. Face-to-face interviews were performed by trained primary care physicians using standardized questionnaires to collect information of potential risk factors at baseline entry. Multi-variable logistic regression models and restricted cubic spline (RCS) were used to evaluate risk factors associated with early-onset colorectal neoplasm. Results: 124 cases of early-onset colorectal neoplasm including six CRC cases and 118 colorectal adenomas (CRA) cases were detected between 2012 and 2016. We found that sex, body mass index (BMI), and family history of CRC were associated with early-onset of colorectal neoplasm. RCS model showed a positive dose-response and linear association between the level of BMI and the early-onset colorectal neoplasm risk among the young participants (P-overall = 0.19, P-non-linear = 0.97). Conclusion: The findings indicate that it is beneficial for average people to start opportunistic CRC screening younger than 50 years. As for those at high risk, increased surveillances are strongly recommended. Further close follow-up is required for research on the underlying causes of early-onset CRC.